SPA_LOW_SKY – Creative Commitment as a Studying Environment in an Artistic Meeting Zone - Laven, Rolf (Farol, 2022)
With the participation of artists, schools and local residents, an artistic encounter zone is being created between a sculpture studio in Vienna's Spalowskygasse and the "Lerncampus Mariahilf". This artistic intervention, inspired by Rolf Laven, is presented as an innovative form of learning that uses the school space and employs service learning/engaged learning approaches. Based on cultural heritage and local history, methods are developed with different upcycling materials. Such an artistic encounter zone initiates a public creative dialogue. It aims to expand the circle of participants beyond already established knowledge alliances (Erasmus+ KA2 research projects Rural 3.0_Service-Learning; SLUSIK and SLIDE as well as artistic, school and student teaching-learning areas) and co-creators and to create new synergies. The project concept envisages broad participation from the field of art and cultural work, from school and university institutions as well as from social institutions. Participants are invited to take the initiative for community learning activities.
Keywords: Service-Learning; Third Mission Art & Participation; Social Sculpture; Empowerment; Sustainability and Engagement; Art Symposium